Behavioral and Memory enhancing effects of Memory Enhancing Milk Toffee Developed by Incorporation of O. bracteatum Extract - Raza, Rashid; Arif, Minhal; Hanif, Hibah; Aslam, Eruj; Baig, Amjad (Journal of Research (Science), 2025)
Product development, is the life-blood of companies and societies. The present study was designed to explore the behavioral and memory enhancing effects of the first ever nutraceutical (memory enhancing) milk toffee produced by incorporating of Eastern Medicine O. bracteatum. The results were compared with the efficacy of Eastern khamira-e-gaozaban amberi. Experimental animal mice administered with milk toffee and ware gone through various CNS parameters to check the effects. The effects of both were recorded on day 20 and 30. To the first group dose of milk toffee was 0.05gm without dilution and 0.83 mg dissolved in milk was administered to second group, and the third one was control. A distinct decrease in time in the stationary rod test was observed by both newly prepared milk toffee as well as khamira, while exploratory activities such as cage crossing, open field and head dip activities were found to be increased in the test animal. The newly produced milk toffee possesses memory enhancing effect and improved behavior effects